2020
DOI: 10.3390/jmse8100760
|View full text |Cite
|
Sign up to set email alerts
|

Coral Reef Community Changes in Karimunjawa National Park, Indonesia: Assessing the Efficacy of Management in the Face of Local and Global Stressors

Abstract: Karimunjawa National Park is one of Indonesia’s oldest established marine parks. Coral reefs across the park are being impacted by fishing, tourism and declining water quality (local stressors), as well as climate change (global pressures). In this study, we apply a multivariate statistical model to detailed benthic ecological datasets collected across Karimunjawa’s coral reefs, to explore drivers of community change at the park level. Eighteen sites were surveyed in 2014 and 2018, before and after the 2016 gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 43 publications
1
27
0
3
Order By: Relevance
“…The combination of object detection and object tracking can enhance animal movement ecology through the streamlined collection of several sets of ecological information (Botella et al, 2018;Christin et al, 2019), and this new data may revolutionize ecological studies. Traditional presence/absence data can be used, for example, to understand the environmental drivers of a species' geographic distribution, and the collection of presence/absence data from videos can easily be automated (González-Rivero et al, 2020;Kennedy et al, 2020;Schneider et al, 2018Schneider et al, , 2019. However, presence/absence data alone cannot inform about how multiple ecological processes interact, and presence/absence data conflate movement of individuals with mortality (Zurell et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The combination of object detection and object tracking can enhance animal movement ecology through the streamlined collection of several sets of ecological information (Botella et al, 2018;Christin et al, 2019), and this new data may revolutionize ecological studies. Traditional presence/absence data can be used, for example, to understand the environmental drivers of a species' geographic distribution, and the collection of presence/absence data from videos can easily be automated (González-Rivero et al, 2020;Kennedy et al, 2020;Schneider et al, 2018Schneider et al, , 2019. However, presence/absence data alone cannot inform about how multiple ecological processes interact, and presence/absence data conflate movement of individuals with mortality (Zurell et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…1) [119]. In Karimunjawa National Park, Indonesia, a multivariate statistical model was applied to examine community composition changes and concluded that water quality management across the park is critical to improving resiliency [123]. Lastly, statistical models were used to investigate various coral taxa's responses to local stressors and climate variability in the Red Sea.…”
Section: Creating Risk Assessmentsmentioning
confidence: 99%
“…Furthermore, the dataset offers human-classified annotations and images that can be used to train and validate automated image classifiers. The dataset and imagery have contributed to a substantial number of publications 23 , 25 , 35 39 . The ultimate goal of this record is to expedite scientific investigation and evidence-based management.…”
Section: Background and Summarymentioning
confidence: 99%